2013
DOI: 10.1007/s12298-013-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid and salicylic acid sensitive and insensitive catalases in different genotypes of chickpea against Fusarium oxysporum f. sp. ciceri

Abstract: Differential expression of catalase isozymes in different genotypes of chickpea resistant genotypes- A1, JG-315, JG-11, WR-315, R1-315, Vijaya, ICCV-15017, GBS-964, GBM-10, and susceptible genotypes- JG-62, MNK, ICCV-08321, ICCV-08311, KW-104, ICCV-08123, ICC-4951, ICC-11322, ICC-08116 for wilt disease caused by Fusarium oxysporum. f. sp. ciceri (Foc) was analyzed. Salicylic acid (SA) and H2O2 concentrations were determined in control as well as in plants infected with F. ciceri and found that the high and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In support, Rao et al (1997) found that SA treatment in A. thaliana elevated the H 2 O 2 content and H 2 O 2 -metabolizing enzymes depended upon the dose of SA concentration and time-duration [ 50 ]. In plants, the various CAT present multiple isoforms with different activities in diverse plant organs [ 53 , 54 , 55 ]. CAT isozymes of chickpea plant were sensitive to SA differently, because SA was a specific inhibitor of CAT activity both in shoot and root [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support, Rao et al (1997) found that SA treatment in A. thaliana elevated the H 2 O 2 content and H 2 O 2 -metabolizing enzymes depended upon the dose of SA concentration and time-duration [ 50 ]. In plants, the various CAT present multiple isoforms with different activities in diverse plant organs [ 53 , 54 , 55 ]. CAT isozymes of chickpea plant were sensitive to SA differently, because SA was a specific inhibitor of CAT activity both in shoot and root [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monofunctional CAT has a common action that converts H 2 O 2 into H 2 O and O 2 in two steps, while bifunctional, in addition to the usual CAT activity, also exhibits peroxidase activity with an electron donor present [103]. The different response of CAT between shoots and roots is also discussed in the research conducted by Gayatridevi et al [104]. After exposure to salicylic acid and Fusarium sp., they observed a different number of CAT isoforms in shoots and roots in different genotypes of Cicer arientum L. In addition, they determined a significant difference between shoots and roots in sensitivity to salicylic acid, as well as the activities of individual isoforms were completely inhibited by individual treatment.…”
Section: Se Effect On Wheat Oxidative Status and Antioxidative Responsementioning
confidence: 97%